2020
DOI: 10.1002/aoc.6011
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of novel hybrid nanomaterials based on LaFeO3 and phosphotungstic acid as a highly efficient magnetic photocatalyst for the degradation of methylene blue dye solution

Abstract: Novel magnetic hybrid nanomaterials 1 (LaFeO3.Fe3O4@SiO2‐NH2/PW12) were synthesized by supporting phosphotungstic acid (H3PW12O40; PW12) on LaFeO3.Fe3O4 nanomaterials through sono‐assisted method. The synthesized nanomaterials were fully characterized by using FT‐IR, XRD, UV–vis, BET‐BJH, VSM, SEM, and TEM analyses. FT‐IR, XRD, and UV–vis confirmed successful synthesis of nanomaterials. The SEM and TEM images revealed spherical morphology with core‐shell structure for hybrid nanomaterials 1. VSM results confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…[25] The rapid recombination of electrons and holes has occurred in pure Fe 3 O 4 , which decreases its photocatalytic efficiency. [26] To overcome those issues, a simple approach is to combine with a p-type semiconductor to form semiconductor-polymer nanostructures also called p-n junction composites. As previous studies showed, the polymer/magnetic particle composite photocata-lysts expand the light absorption range and increase the light absorption rate.…”
Section: Introductionmentioning
confidence: 99%
“…[25] The rapid recombination of electrons and holes has occurred in pure Fe 3 O 4 , which decreases its photocatalytic efficiency. [26] To overcome those issues, a simple approach is to combine with a p-type semiconductor to form semiconductor-polymer nanostructures also called p-n junction composites. As previous studies showed, the polymer/magnetic particle composite photocata-lysts expand the light absorption range and increase the light absorption rate.…”
Section: Introductionmentioning
confidence: 99%